Towards a Newborn Screening Common Data Model: The Utah Newborn Screening Data Model - David Jones; Jianyin Shao; Heidi Wallis; Cody Johansen; Kim Hart; Marzia Pasquali; Ramkiran Gouripeddi; Andreas Rohrwasser (MDPI AG, 2021)
As newborn screening programs transition from paper-based data exchange toward automated, electronic methods, significant data exchange challenges must be overcome. This article outlines a data model that maps newborn screening data elements associated with patient demographic information, birthing facilities, laboratories, result reporting, and follow-up care to the LOINC, SNOMED CT, ICD-10-CM, and HL7 healthcare standards. The described framework lays the foundation for the implementation of standardized electronic data exchange across newborn screening programs, leading to greater data interoperability. The use of this model can accelerate the implementation of electronic data exchange between healthcare providers and newborn screening programs, which would ultimately improve health outcomes for all newborns and standardize data exchange across programs.